Tracking Basic Education Expenditure in Yemen : Analyses of Public Resource Management and Teacher Absenteeism - World Bank (Washington, DC, 2012)
Yemen faces significant challenges in expanding access and promoting quality for improved educational outcomes. The study employs both qualitative and quantitative methods to provide recommendations for tracking public expenditure and improving service delivery in the basic education sector in Yemen. To this end, it documents the management of public resources in Yemen's education sector and potential inefficiencies in the use of these resources. This report, through its various components, revealed significant impediments-teacher deployment and salary payment, materials provision, student and teacher attendance, among others-on the path to improving education service delivery in Yemen. This study examines four main research issues related to Yemen's education sector: 1) leakage in the flow of funds, 2) compliance with financial management standards, 3) incentives to provide better quality services, and 4) teacher management issues. The study investigates the disparities and inconsistencies between formal regulations and informal practices in teacher deployment, wage payments, and resource allocations to schools. The study explores how absenteeism correlates with a wide range of potential determinants of the quality of education at the individual, facility, and national levels.